Land-use effects on phosphorus fractions in cerrado oxisols - Neufeldt, Henry; Silva, J.E. da; Ayarza, Miguel Angel; Zech, W. (Springer, 2000)
Differently managed oxisols from Central Brazil were studied using a sequential P fractionation procedure because the effects of land use on the distribution of P forms in these soils are barely known. Therefore levels of labile and recalcitrant P forms in the natural Cerrado savanna were compared with those of crop, pasture and reforestation sites on differently textured oxisols. Under natural conditions of strong P deficiency, >60% of labile P was organic P (Po), reflecting the high contribution of Po to plant nutrition. Fertilisation after land-use change only increased levels of inorganic P (Pi) forms, the increase being most accentuated in the labile Pi fraction. At the crop and the pasture sites P tended to accumulate as recalcitrant P forms in the clayey soils, while in the loamy soils there was only a minor enrichment, probably due to the lower amounts of Fe- and Al-(hydr)oxides. In the reforestation sites, labile P was maintained at high levels, most likely through efficient recycling of the litter. The P fractionation procedure was also applied to particle-size fractions which reflected P transformations along an organic and mineralogical gradient. The clay fraction corresponded to 69–87% of total P and appeared to be both a sink for highly recalcitrant P and a source for labile P, especially labile Po. The sequential P fractionation procedure was also an effective method with which to detect the presence of fertiliser-P residues in the coarse-silt fraction.